Body Mass Index and Weight Loss in Overweight and Obese Korean Women: The Mediating Role of Body Weight Perception - Sunjoo Boo, RN, PhD (Elsevier, 2013)
Purpose: This study were to assess the relationships among BMI, body weight perception, and efforts to lose weight in a public sample of Korean women who are overweight and obese and to examine the mediating role of body weight perception on the relationship between BMI and weight loss efforts. Methods: This cross-sectional study used data from the 2008 Korea National Health and Nutrition Examination Survey. The sample was 1,739 Korean women 20 years old or older with body mass index (BMI) ≥ 23 kg/m2. Bivariate relationships among variables of interests were assessed. Three separate regressions were used to test the mediating role of body weight perception on the relationship between BMI and weight loss efforts. Results: BMI and body weight perception were significant correlates of weight loss efforts. BMI was significantly associated with weight perception, but a large proportion of women underestimated their weight. Weight perception partially mediated the relationship between BMI and weight loss efforts in Korean women. Conclusion: In light of the high prevalence of overweight or obesity and the many health consequences associated with obesity, Korean women should be aware of a healthy body weight and try to achieve that weight. Nursing interventions should consider body weight perception to effectively motivate overweight and obese Korean women to lose weight, as necessary.